Palestinian Consumer’s Intention to Recommend a Car Brand and its Relationship to Perceived Risks when Buying a Car - Hoor, Ahmad Ibrahim (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This study looks at what kind of strategies are more effective to reduce the perceived degree of risk, through understanding the correlation between that strategy and type of risks which have an impact on the recommendation intention of the consumer and thus on the final purchase decisions of the buyers. The empirical work involved observing behavior of car owners in Palestine through data gathered via a survey utilizing a questionnaire that measures various types of perceived risks associated with purchase of a car, and what risk-reduction strategies are employed by consumers in minimization of such risks, and what effect these have on the recommendation intention of the car owners regarding their car. The results show that the Palestinian consumer depends heavily on spoken word brand name, pricing, and quality strategies to reduce the degree of perceived social and time risks but financial, functional, and physical risks are not reduced by such strategies with the exception of brand name and its reduction of physical risk. Keywords: Recommendation Intention, Perceived Degree of Risk, Consumer Behavior

ÖZ: Müşterilerin nihai satın alma kararını etkileyecek olan tüketicilerin başkalarına ürünü tavsiye etme eğilimi üzerinde yapılan bu araştırma, alışveriş kararında karşılaşılan algılanan risklerin hangi stratejilerle azaltılabileceğini ve hangi stratejilerin hangi riskleri bilhassa azalttığını incelemiş, ve bunun tavsiye eğilimini nasıl etkilediğine bakmıştır. Saha çalışması Filistin‘de arabası olan müşterilerin, kendi satınalma kararları doğrultusunda aynı ürünü başkalarına tavsiye etme eğilimlerini, ve tüketicilerin ürün alırken hangi algılanan risklerle ve ne yoğunlukta karşılaştıklarını, ve bu riskleri en aza indirgemek için en tür stratejilere ne kadar ağırlık verdiklerini ölçmüştür. Sonuçlardan görüleceği gibi Filistinli tüketiciler ağırlıklı olarak ağızan ağıza tavsiye, marka ismi, fiyatlandırma, ve kalite stratejilerine dayanarak sosyal ve zaman risklerini azaltma yoluna gitmişler, ancak bunun mali, fonksiyonel, ve fiziksel risklere bir azaltıcı etkisi gözlemlenmemiştir. Buna tek istisna, marka ismi stratejisi ve fiziksel riske olan azaltıcı etkisidir. Anahtar kelimeler: öneri niyeti, risk algıladıkları derecesi, tüketici davranışları.
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Assist. Prof. Dr. Mehmet İslamoğlu.
Keywords: Business Administration; Consumer Behavioo - Car Brands; Recommendation Intention; Perceived Degree of Risk; Consumer Behavior